КОМП'ЮТЕРНЕ МОДЕЛЮВАННЯ ПЕРЕХІДНИХ ЕЛЕКТРОМЕХАНІЧНИХ ПРОЦЕСІВ У ВІТРОЕНЕРГЕТИЧНІЙ УСТАНОВЦІ ІЗ МАГНІТНИМ РЕДУКТОРОМ - Гребеніков, В.В.; Подольцев, О.Д.; Гамалія, Р.В.; Тажибаев, А.А.; Аринов, Н.Н.; Сахно, О.А. (Інститут електродинаміки НАН України, Київ, 2024)
In this work, a computer Simulink model of a wind power plant has been developed, which uses a magnetic gearbox instead of a mechanical gearbox and also contains a synchronous permanent magnet generator. A separate Simulink model of a magnetic gearbox built on the basis of a modulated magnetic field in the air gap was developed, which allows to study the stability of its operation both in steady-state and transient modes. Calculations of various dynamic modes of the wind power plant’s operation were carried out, based on the developed model, such as the starting mode, an instantaneous increase in the wind speed acting on the wind turbine, and an increase in the load of the electric generator. According to the results of the calculations, it is shown that in transient modes, when short-term overloads occur, both rotors of the magnetic gearbox can fall out of synchronous motion for a certain period of time and then, depending on the parameters of the gearbox (as well as its other elements), the electromechanical system either reaches a certain operating steady-state mode or loses the ability to transfer mechanical power from the wind turbine to the generator. It has been shown that the use of a more powerful magnetic gearbox, with an increased value of the maximum magnetic torque, allows of a more overload-resistant operation of both: a gearbox and the wind plant as a whole. References 9, figures 10.